Case Study : Rojak Khadijah YK / Muhd Daim Bahanudin - Bahanudin, Muhd Daim (2021)
Lets support Khadijah YK’s business because the products are so delicious because I already tasted the ‘Rojak’ and all the customers who buy the products vey satisfy with it and repeats the order so many times. The price is only RM 5 each and it very reasonable because it vey delicious and have a normal and nice packaging